2017
DOI: 10.21037/jgo.2017.08.09
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated assessment of sarcopenia using psoas area and density predicts outcomes after pancreaticoduodenectomy for pancreatic malignancy

Abstract: Background: Sarcopenia has been associated with increased adverse outcomes after major abdominal surgery. Sarcopenia defined as decreased muscle volume or increased fatty infiltration may be a proxy for frailty. In conjunction with other preoperative clinical risk factors, radiographic measures of sarcopenia using both muscle size and density may enhance prediction of outcomes after pancreaticoduodenectomy (PD) for malignancy. Methods: Preoperative computed tomography (CT) scans of patients undergoing PD for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
1
34
1
3
Order By: Relevance
“…Muscle Hounsfield units measured on CT scans can be used to predict muscle density, which represents the intra-muscular adipose infiltration. 41 It has been shown to correlate with adverse outcomes in patients undergoing pancreatic surgery, 7,42 but in our study, we did not find an association between lower muscle density and worse outcomes. But PMD decreased significantly after the operation, which represented higher fat infiltration in muscle or myosteatosis because of the inflammation-induced consumption of muscle protein and fat deposition.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Muscle Hounsfield units measured on CT scans can be used to predict muscle density, which represents the intra-muscular adipose infiltration. 41 It has been shown to correlate with adverse outcomes in patients undergoing pancreatic surgery, 7,42 but in our study, we did not find an association between lower muscle density and worse outcomes. But PMD decreased significantly after the operation, which represented higher fat infiltration in muscle or myosteatosis because of the inflammation-induced consumption of muscle protein and fat deposition.…”
Section: Discussioncontrasting
confidence: 74%
“…4 , 5 A recent European consensus definition of sarcopenia described computed tomography (CT) as the gold standard for estimating muscle mass and some research also showed that CT-determined sarcopenia linked to poor outcomes following pancreatic surgery. 6 , 7 Sarcopenic overweight/obesity is another clinical problem characterized by the coexistence of overweight or obesity and sarcopenia which has been proven to be a strong predictor of major complications after pancreatoduodenectomy. 8 , 9 So, the International Study Group of Pancreatic Surgery recommend assessment of both sarcopenia and sarcopenic obesity prior to pancreatic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Van Dijk et al could link a low MA to reduction of survival in 199 patients [29]. Namm et al showed similar results applying a semi-automated technique in 116 patients [33]. Sui et al linked sarcopenia as defined by total muscle area to the 5 year survival [34].…”
Section: Discussionmentioning
confidence: 99%
“…The association between sarcopenia and postoperative complications including fistulas (a common and severe problem following PD) has also been shown [15e19]. In addition, Namm showed that following a pancreaticoduodenectomy, sarcopenic patients are more likely to be discharged to a nursing facility instead of independent living [19].…”
Section: Frailty Screening Tools and Hbp Surgerymentioning
confidence: 99%